Pengaruh Latihan Skipping Rope dan Latihan Shadow Terhadap Kelincahan Atlet Bulutangkis - Nofiansyah, Ega Ega; Komarudin, Komarudin; Hidayah, Nidaul (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The aim of this research was to determine the effect of skipping rope training and shadow training on the agility of badminton athletes and to determine the difference in the effect of skipping rope training and shadow training on the agility of badminton athletes. The method used in this research is an experimental method with a two-group pretest-posttest group design. The population in this study were UPI Badminton UKM athletes. The sample consisted of 40 athletes taken using purposive sampling technique. The instrument in this research used the Court Agility Test. The statistical analysis used is the Paired Sample t-test and the Independent Sample t-test. The results of this study show that skipping rope training has a significant influence on the agility of badminton athletes, shadow training has a significant influence on the agility of badminton athletes, and there is no significant difference in the effect between skipping rope training and shadow training on the agility of badminton athletes. The conclusion is that both Skipping Rope training and Shadow training can increase agility. Keywords: Agility, Badminton Skipping Rope, Shadow